Global value chains, large-scale farming, and poverty: Long-term effects in Senegal - Goedele Van den Broeck; Johan F. M. Swinnen; Miet Maertens (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2016)
This paper is the first to present panel data evidence on the longer-term impact of expansion of global value chains and large-scale export-oriented farms in developing countries. Using panel data from two survey rounds covering a seven-year period and fixed effects regression, we estimate the longer-term income effects of wage employment on large-scale farms in the rapidly expanding horticultural export sector in Senegal. In addition to estimating average income effects, we estimate heterogeneous income effects using fixed effects quantile regression. We find that poverty and inequality reduced much faster in the research area than elsewhere in Senegal. Employment in the horticultural export sector significantly increases household income and the income effect is strongest for the poorest households. Expansion of the horticultural export sector in Senegal has been particularly pro-poor through creating employment that is accessible and creates substantial income gains for the poorest half of the rural population. These pro-poor employment effects contrast with insights in the literature on increased inequality from rural wage employment.
Keywords: F16; J14; O19; Q17; R23; 330; globalisation; high-value supply chains; rural wage employment; quantile regression; panel data; long-term effects